Problems of Regional Development of Protected Areas in the Yamalo-Nenets Autonomous Okrug - N. Morgun, Evgenia (2019)
The paper briefly overviews the development of the regional network of protected areas (PAs) in Yamalo-Nenets Autonomous Okrug (YNAO). The network of PAs of YNAO includes PAs with a variety of statuses (federal, regional, and local importance) and categories (from natural monument to nature reserve), which are intended to prevent irreversible processes in ecosystems and ensure the conservation and balanced use of natural resources. Protected areas are distributed across the YNAO unevenly, and functionally, they only weakly link elements of ecosystems and landscapes into a unified natural and economic system that preserves the biological and landscape diversity. Very few protected areas have been established in wetlands that are candidates for inclusion in the list of Ramsar sites. Optimization of protected areas and amendment of their boundaries involves the integration of approaches and targeted coordinated research by professionals in a variety of fields. Obtaining evidence-based, stable time series of variables that characterize natural and natural-anthropogenic YNAO ecosystems requires coordinated, comprehensive, and prolonged research projects across all the existing protected areas and areas to be protected in the future. The zoning of the Yamalsky State Natural Sanctuary of Regional (Okrug) Importance should be revised. In the future, transboundary protected areas should be established with the Republic of Komi and Krasnoyarsk Krai. Another pressing concern is the need for an integrated survey of island ecosystems and landscapes to prepare a feasibility study for the establishment of Arctic Island Marine Nature Reserve that will include the islands Bely, Vilkitsky, Shokalsky, and Neupokoev.